Risk Agent Kecelakaan Kapal Dalam Klasifikasi Kesalahan Manusia - Yahya, Shanty (Majalah Ilmiah Gema Maritim, 2023)
Sea transportation is the primary means of transporting goods because of its lower costs and high accessibility. The use of ships in sea transportation has increased national and international trade. However, increased trade is not in line with shipping safety. Until now, sea transportation still poses risks in shipping. The risk is that the ship experiences an accident while sailing. Ship accidents are always a threat to shipping safety, the economy, and society because of their very detrimental impacts. Many factors cause ship accidents. One of these factors is human error. Human error in ship accidents is based on several factors. This research aims to classify the Risk Agent (RA) of ship accidents due to human error. The method used was a chronological review of 200 accident cases, questionnaires, interviews, and forum group discussions. The results obtained in this research were that the crew did not calculate the stability of the ship after loading, the arrangement and arrangement of the cargo on board did not comply with the stowage plan, the crew's skills and knowledge were lacking, and safety drills were not carried out, which is RA in the category of often being the cause of ship accidents. Meanwhile, due to carelessness in checking crew certificates, the ship's crew did not record the condition of the ship's machinery during guard duty, the equipment was operated beyond the standard time, the ship's sailing experience was lacking, they were not familiar with shipping lanes, and the ship's crew experienced fatigue, which was included in the medium category.